2017
DOI: 10.1016/j.ygyno.2016.10.036
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of alisertib (MLN8237) in recurrent or persistent uterine leiomyosarcoma: An NRG Oncology/Gynecologic Oncology Group study 0231D

Abstract: Objective This two-stage Phase II study assessed the activity of single agent alisertib in patients with recurrent/persistent uterine leiomyosarcoma (uLMS). Methods Eligibility criteria included histologically-confirmed, recurrent or persistent uLMS, age ≥18, 1-2 prior cytotoxic regimens, and RECIST version 1.1 measurable disease. The primary objective of the study was to evaluate the efficacy of alisertib through the frequency of patients with objective tumor responses and the frequency who survived event-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…While alisertib demonstrated preclinical activity against pediatric solid tumors including ES, it did not meet study criteria for significant benefit in single‐agent use in clinical trials . In those studies, because of the myelosuppression caused by the drug at the maximally tolerated dose, it was administered for 7 days followed by 2 weeks of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While alisertib demonstrated preclinical activity against pediatric solid tumors including ES, it did not meet study criteria for significant benefit in single‐agent use in clinical trials . In those studies, because of the myelosuppression caused by the drug at the maximally tolerated dose, it was administered for 7 days followed by 2 weeks of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Phase 1 pediatric clinical trial, alisertib had higher toxicity in children than in adults, limiting its maximally tolerated dose . Alisertib failed to meet response criteria in multiple Phase 2 studies when used alone, but next‐generation inhibitors of AURKA are in development, and AURKA inhibition in combination with other treatment approaches may be particularly effective against ES.…”
Section: Introductionmentioning
confidence: 99%
“…Although alisertib showed preclinical antitumor efficacy, it failed to show meaningful activity in single-agent use in multiple clinical trials [18] , [21] , [45] , in which it was administered for 7 days with 14 days of recovery. We have shown that alisertib treatment induces rebound transcriptional and protein overexpression of its targets, which may be a mechanism of resistance against the drug and account for the lack of clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the Phase 1 pediatric clinical trial, it had higher toxicity in children than in adults, limiting its maximally tolerated dose [17] . Alisertib failed to meet response criteria in multiple phase 2 studies when used alone [18] , [19] , [20] , [21] but is being examined in combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Although alisertib showed preclinical antitumor efficacy, it failed to show meaningful activity in single-agent use in multiple clinical trials 18,44,45 , in which it was administered for 7 days with 14 days of recovery. We have shown that alisertib treatment induces rebound transcriptional overexpression of its targets, which may account for the lack of clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%